Halomonas gemina sp. nov. and Halomonas llamarensis sp. nov., two siderophore-producing organisms isolated from high-altitude salars of the Atacama Desert - Hintersatz, Christian; Singh, Shalini; Rojas, Luis Antonio; Kretzschmar, Jerome; Wei, Sean Ting-Shyang; Khambhati, Khushal; Kutschke, Sabine; Lehmann, Falk; Singh, Vijai; Jain, Rohan; Pollmann, Katrin (Frontiers in Microbiology, 2023)
This study aimed to discover novel siderophore-producing organisms with the ability to produce high amounts of the iron-binding compounds. In the course of this, two not yet reported halophilic strains designated ATCHAT and ATCH28T were isolated from hypersaline, alkaline surface waters of Salar de Llamará and Laguna Lejía, respectively. As an alkaline milieu greatly reduces the bioavailability of iron, organisms native to those environments were suspected to produce greater amounts of siderophores to sequester the essential element. Both strains were characterized utilizing a polyphasic approach and further investigated to assess their ability to secrete siderophores. Comparative analysis of the 16S rRNA gene sequences revealed that the isolates belonged to the genus Halomonas. ATCHAT was closely related to Halomonas. salicampi and Halomonas vilamensis, while ATCH28T was related closest to Halomonas ventosae and Halomonas salina. Utilizing the chromeazurol S liquid assay, both strains were shown to produce iron-binding compounds. Via NMR and genomic analysis, the siderophore synthesized by strain ATCH28T has been determined to be desferrioxamine E (DFOE). Although this siderophore is common for various terrestrial microorganisms, it has not yet been reported to occur within Halomonas, making strain ATCH28T first member of the genus to produce a non-amphiphilic siderophore. Furthermore, the effect of various media components on the secretion of DFOE was investigated and obtained concentrations could be increased to more than 1000 µM of the compound. Genomic analysis of strain ATCHAT revealed the presence of a not yet reported NRPS-dependant gene cluster responsible for the secretion of siderophore. However, the strain only secreted small amounts of the iron-binding compound and therefore its siderophore was not investigated exhaustively within the scope of this study. Based on their phenotypic and genotypic characteristics, both strains unambiguously differed from other described members of the genus Halomonas. Average nucleotide identity (ANI) values and levels of DNA-DNA relatedness clearly indicated that the strains represented two novel species. Hence, both species should be added as new representatives of the genus Halomonas, for which the designations Halomonas llamarensis sp. nov. (type strain ATCHAT=DSM 114476=LMG 32709) and Halomonas gemina sp. nov. (type strain ATCH28T=DSM 114418=LMG 32708) are proposed.